2017
DOI: 10.3847/2041-8213/aa8d14
|View full text |Cite
|
Sign up to set email alerts
|

High-energy Neutrino Emission from Short Gamma-Ray Bursts: Prospects for Coincident Detection with Gravitational Waves

Abstract: We investigate current and future prospects for coincident detection of high-energy neutrinos and gravitational waves (GWs). Short gamma-ray bursts (SGRBs) are believed to originate from mergers of compact star binaries involving neutron stars. We estimate high-energy neutrino fluences from prompt emission, extended emission, X-ray flares, and plateau emission, and show that neutrino signals associated with the extended emission are the most promising. Assuming that the cosmic-ray loading factor is ∼ 10 and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
169
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 142 publications
(174 citation statements)
references
References 70 publications
4
169
1
Order By: Relevance
“…under the approximation f mes (ε A ) f pγ (ε A /A). The suppression factor accounts for the energy cooling on the primary pions and secondary muons, f sup f sup,π f sup,µ [117]. The pion cooling suppression factor is calculated as f sup,π = 1 − exp(−t π,cool /t π,decay ), where t π,decay is the decay time scale of pions.…”
Section: 116]mentioning
confidence: 99%
“…under the approximation f mes (ε A ) f pγ (ε A /A). The suppression factor accounts for the energy cooling on the primary pions and secondary muons, f sup f sup,π f sup,µ [117]. The pion cooling suppression factor is calculated as f sup,π = 1 − exp(−t π,cool /t π,decay ), where t π,decay is the decay time scale of pions.…”
Section: 116]mentioning
confidence: 99%
“…Whereas SGRBs are mainly detected as short hard bursts with a duration of ∼ < 2 s (e.g., Piran 2004;Nakar 2007;Gehrels et al 2009;Berger 2014;Ackermann et al 2013), it is known that a good fraction of SGRBs have late-time emission such as extended softer emission, X-ray flares, and plateaus (Evans et al 2009;Chincarini et al 2010;Margutti et al 2011;Sakamoto et al 2011;Rowlinson et al 2013;Kagawa et al 2015;Kaneko et al 2015;Lien et al 2016;Kisaka et al 2017), and even longer mysterious X-ray excess emission was reported for GRB 130603B (Fong et al 2014), which is known to be coincident with the kilonova/macronova candidate (Berger et al 2013;Tanvir et al 2013). Resulting GeV-TeV gamma-ray emission Murase et al 2011) and high-energy neutrino emission (Murase & Nagataki 2006;Kimura et al 2017) have also been studied.…”
Section: Introductionmentioning
confidence: 97%
“…Further checks whether PEs are powered by the dissipation of jet-like outflows or not may be done by detecting early-time X-ray counterparts of NS mergers without prompt γ-ray emission (Matsumoto & Kimura 2018) or searching for nebular emission formed by the central engine (Murase et al 2018). Finally, the prolonged engine activities in the PE phase can be also probed by long-lasting high-energy γ-ray and perhaps neutrino counterparts (Kimura et al 2017;Murase et al 2018;Kimura et al 2019). Table A1.…”
Section: Summary and Discussionmentioning
confidence: 99%